Identification of loci of pseudomonas syringae pv. actinidiae involved in lipolytic activity and their role in colonization of kiwifruit leaves - Patel, Hitendra Kumar (2019)
Bacterial canker disease caused by Pseudomonas syringae pv. actinidiae, an emerging pathogen of kiwifruit plants, has recently brought about major economic losses worldwide. Genetic studies on virulence functions of P. syringae pv. actinidiae have not yet been reported and there is little experimental data regarding bacterial genes involved in pathogenesis. In this study, we performed a genetic screen in order to identify transposon mutants altered in the lipolytic activity because it is known that mechanisms of regulation, production, and secretion of enzymes often play crucial roles in virulence of plant pathogens. We aimed to identify the set of secretion and global regulatory loci that control lipolytic activity and also play important roles in in planta fitness. Our screen for altered lipolytic activity phenotype identified a total of 58 Tn5 transposon mutants. Mapping all these Tn5 mutants revealed that the transposons were inserted in genes that play roles in cell division, chemotaxis, metabolism, movement, recombination, regulation, signal transduction, and transport as well as a few unknown functions. Several of these identified P. syringae pv. actinidiae Tn5 mutants, notably the functions affected in phosphomannomutase AlgC, lipid A biosynthesis acyltransferase, glutamate–cysteine ligase, and the type IV pilus protein PilI, were also found affected in in planta survival and/or growth in kiwifruit plants. The results of the genetic screen and identification of novel loci involved in in planta fitness of P. syringae pv. actinidiae are presented and discussed.